ZrO 2 Nanoparticle Embedded Low Silver Lead Free Solder Alloy for Modern Electronic Devices - Sharma, Ashutosh; Yu, Hakki; Cho, In Sun; Seo, Hyungtak; Ahn, Byungmin (Electronic Materials Letters, 2019)
Abstract: In this article, the authors present the synthesis of Sn–1.0Ag–0.5Cu (SAC105) alloy embedded with zirconium oxide nanoparticles using simple mechanical blending and casting route. The cast samples were characterized in terms of microstructural evolution, wetting, microhardness, and drop test reliability. The characterizations were performed by using a tabletop X-ray diffraction, field emission scanning electron microscope, and the compositions were identified by energy dispersive spectroscopy. The results showed that addition of ZrO 2 nanoparticles significantly refines the grain size, Ag 3 Sn, and Cu 6 Sn 5 intermetallic compounds thickness by 46, 14, and 26% respectively as compared to the single component SAC105 alloy. The results were also compared with those of standard Sn–3.0Ag–0.5Cu (SAC305) alloy. Although the spreading and microhardness of SAC105 is found to be slightly poor or comparable to SAC305 yet drop test reliability can be improved significantly after addition of ZrO 2 nanoparticles appreciably. This kind of refinement results in a cheap alternative to SAC305 with comparable mechanical strength and high solder joint reliability. Graphical Abstract: [Figure not available: see fulltext.]
Keywords: Drop test reliability; Electronic device; Field emission scanning electron microscopes; Lead-free solder alloy; Mechanical blending; Oxide nanoparticles; Solder joint reliability; ZrO2 nanoparticles; Electronics; Intermetallic; Low silver; Melting; Microhardness; Microstructure; Nanoparticle